Analysing Employee Retention and Motivation Strategies in Private Sectors in Oman - Al-Mukhaini, sumaiya; Al-Hadrami, Ahmed; Al-Hadrami, Naila (Social Empowerment Journal, 2025)
The research has investigated the effectiveness of employee retention as well as motivation strategies in context of the private sector of Oman by aiming at identifying the challenges alongside opportunistic practices. Through the combination of interviews with HR Managers and relevant employees in addition to the secondary qualitative literature study analysis, the study has exhibited the findings that how motivational strategies would be impacting loyalty, productivity as well as performances and satisfaction among the employees in context of Omani private sector organisations. Findings have also suggested although retention strategies are being recognised widely the financial resources constraints in terms of budget is creating challenges for the strategies to not be implemented properly always. Thus, considering organisational culture, rewards competitively alongside career progression as motivational strategies would support recommended on-boarding strategies to ensure ultimate workforce stability in Oman alongside growth in private sector performances.